2013
DOI: 10.1182/blood-2012-04-423418
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib is associated with a reduced incidence of BCR-ABL mutations vs imatinib in patients with newly diagnosed chronic myeloid leukemia in chronic phase

Abstract: Key Points Frontline nilotinib led to fewer, less diverse BCR-ABL mutations than imatinib in patients with chronic myeloid leukemia in chronic phase. Rates of progression to accelerated phase/blast crisis were lower with nilotinib than imatinib in patients with emergent BCR-ABL mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 30 publications
4
66
0
4
Order By: Relevance
“…Since previous studies have suggested that 2nd-TKIs inhibit the proliferation of CML cells with BCR-ABL1 KD mutations [41], it is possible that the introduction of 2nd-TKIs actually led, at least in part, to the lower frequency of BCR-ABL1 KD mutations in our study.…”
Section: Discussionmentioning
confidence: 59%
“…Since previous studies have suggested that 2nd-TKIs inhibit the proliferation of CML cells with BCR-ABL1 KD mutations [41], it is possible that the introduction of 2nd-TKIs actually led, at least in part, to the lower frequency of BCR-ABL1 KD mutations in our study.…”
Section: Discussionmentioning
confidence: 59%
“…The frequency of treatment‐emergent BCR‐ABL1 mutations detected in ENESTxtnd was comparable to that in nilotinib‐treated patients in ENESTnd (Kantarjian et al , 2011; Hochhaus et al , 2013). By the 2‐year data cut‐off in ENESTnd, treatment‐emergent mutations were detected in 10 patients (3·5%) in the nilotinib 300‐mg twice‐daily arm and 8 patients (2·8%) in the nilotinib 400‐mg twice‐daily arm [ versus 20 patients (7·1%) in the imatinib arm].…”
Section: Discussionmentioning
confidence: 60%
“…By the 2‐year data cut‐off in ENESTnd, treatment‐emergent mutations were detected in 10 patients (3·5%) in the nilotinib 300‐mg twice‐daily arm and 8 patients (2·8%) in the nilotinib 400‐mg twice‐daily arm [ versus 20 patients (7·1%) in the imatinib arm]. Similar to ENESTnd, the majority of patients with treatment‐emergent mutations in ENESTxtnd developed nilotinib‐resistant mutations (i.e., T315I) or mutations less sensitive to nilotinib (i.e., E255, F359, and Y253) (Kantarjian et al , 2011; Hochhaus et al , 2013). …”
Section: Discussionmentioning
confidence: 99%
“…2 In contrast, second-generation TKIs such as nilotinib and dasatinib lead to faster and deeper MRs, 29,30 lower risks of AP/BC transformation, and in the case of nilotinib, lower risk of acquired kinase domain mutations. 31 Second-generation TKIs are often preferred in patients with high Sokal or Hasford risk scores, or when a high priority is placed on the rapid achievement of deep MRs. 32 However, outstanding questions remain over the long-term safety profile of these drugs. Although severe AEs such as vascular disease [33][34][35] or pulmonary toxicities 36,37 occur uncommonly with second-generation TKIs, these AEs lead to significant morbidity when they do occur.…”
Section: Discussionmentioning
confidence: 99%